Exploring the Role of ChatGPT in Enhancing EFL Students’ Writing Skills: A Qualitative Study at Universitas Negeri Semarang - Dzahabiyyah, Launia (Journal of English Language and Education, 2025)
Artificial intelligence (AI) is changing how teachers and students teach and learn English as a Foreign Language (EFL). This is also changing how schools work. Current research primarily examines the advantages of various digital writing assistance tools; however, there has been insufficient exploration of ChatGPT, an AI-driven language model, in the context of Indonesian EFL. This study seeks to investigate the influence of ChatGPT on the writing proficiency of eighth-semester students in the English Education Program at Universitas Negeri Semarang (UNNES). Using a qualitative design, data were collected through in-depth interviews with three subjects and subsequently analyzed thematically. The findings suggest that ChatGPT can enhance students' overall grammatical precision, lexical variety, conceptual organization, and writing confidence; nonetheless, there are apprehensions regarding dependency, originality, and contextual accuracy. The research findings demonstrate that, when employed critically and responsibly in EFL writing instruction, ChatGPT can function as an effective supplementary resource.